Caudal epidural analgesia in calves using different local analgesics - Sarker, K; Hashim, MA; Hossain, MA; Lucky, NS (Journal of the Bangladesh Agricultural University, 2010)
Analgesic effects were conducted with 2% lignocaine hydrochloride (LH), 2% lignocaine hydrochloride with adrenaline (LHA) and 0.5% bupivacaine hydrochloride (BH) in calves of both sexes. Analgesic drugs were injected into caudal epidural space in 30 apparently healthy calves of below one year of age. A total of 30 analgesic trials were done, where heart rate, respiration rate and rectal temperature were monitored. Heart rate and respiratory rate significantly (P<0.05) decreased from preanalgesic values, during caudal epidural analgesia period with 0.5% bupivacaine hydrochloride. Heart rate increased significantly (P<0.001) from preanalgesic values when 2% lignocaine plus adrenaline was used. Only lignocaine hydrochloride showed a short onset, rapid spreading without having any side effect. Duration of analgesia was prolonged with 0.5% bupivacaine hydrochloride compared to other analgesic agent. Drowsiness, tympany and shivering were observed when 0.5% bupivacaine hydrochloride was used. Bupivacaine seemed to be better for longer duration of analgesia compared to lignocaine. But lignocaine hydrochloride may be used for rapid onset of analgesia in calves. Keywords: Analgesia; Onset; Caudal epidural; Calves DOI: 10.3329/jbau.v7i1.4798 J. Bangladesh Agril. Univ. 7(1): 53-56, 2009